The reform of intergovernmental relations on the basis of financial decentralization of public administration in Kazakhstan (Journal of Economic Research & Business Administration, 2016)
In this article the authors considers the reform of intergovernmental fiscalrelations on the basis of finance decentralization of public administrationin Kazakhstan. In the context of the budget unitary economic interests ofthe local authorities depend on the state. The sources of income of localauthorities are intergovernmental transfers, which are allocated by the state.For our country, along with the principles of Unitarianism necessary conceptof fiscal federalism. That, in turn, strengthens state control quality parametersof services to the people and the decentralization of the budget. The introductionof a mixed model of financial and tax structure will enable the developmentof the local financial system, helps to regulate the budget, improvement ofinter-budgetary relations, and on the other hand will reduce the inefficiency ofgovernment regulation and equalization of input and output capacity of local authorities.On the other hand, by increasing the regulatory functions of the centralgovernment provides fiscal independence of local authorities.Formation of an effective system of local funds is directly related withthe development of an effective system of decentralization of the statebudget, and provides sources of income restrictions and costs of powersbetween levels of the budget.
Keywords: State management; decentralization; finance; budgetary relations; the local budget.